Exit-Site Infection Caused by Lysinibacillus Sphaericus: Unusual Organism From A Usual Site - Jangla, Sunayana Mukesh (Annals of Pathology and Laboratory Medicine, 2022)
Exit-site infection is an unwanted complication in patients with an indwelling catheter. However, such an infection by an uncommon organism like Lysinibacillus which is otherwise considered an environmental contaminant needs to be mentioned. Our report describes one such case. The patient was given antibiotic as per antibiotic susceptibility report to which he responded.